Power law statistics in the velocity fluctuations of Brownian particle in inhomogeneous media and driven by colored noise. (25th February 2015) - Kazakevičius, R; Ruseckas, J
Abstract: In this paper we consider the motion of a Brownian particle in an inhomogeneous environment such that the motion can be described by the equation yielding a 1/ f spectrum in a broad range of frequencies. The inhomogeneous environment can be a result, for example, of a linear potential affecting the Brownian particle together with the medium where steady state heat transfer is present due to the difference of temperatures at the ends of the medium. The correlation of collisions between the Brownian particle and the surrounding molecules can lead to a situation where the finite correlation time becomes important, thus we have investigated the effect of colored noise in our model. The existence of colored noise leads to an additional restriction of the diffusion and exponential cut-off of the distribution of particle positions. A narrower power law part in the distribution of the particle positions results in a narrower range of frequencies where the spectrum has power law behavior.